Arbuscular mycorrhizal fungi and mycorrhizal stimulant affect dry matter and nutrient accumulation in bean and soybean plants - Salgado, Fabrício Henrique Moreira (2016)
The adoption of biological resources in agriculture may allow less dependence and better use of finite resources. This study aimed at evaluating the effects of inoculation with arbuscular mycorrhizal fungi native to the Brazilian Savannah associated with the application of mycorrhizal stimulant (7-hydroxy, 4’-methoxy-isoflavone), in the early growth of common bean and soybean. The experiment was carried out in a greenhouse, in a completely randomized design, with a 7 x 2 factorial arrangement, consisting of five arbuscular mycorrhizal fungi species, joint inoculation (junction of all species in equal proportions) and native fungi (without inoculation), in the presence and absence of stimulant. The following traits were evaluated: shoot dry matter, root dry matter, mycorrhizal colonization, nodules dry matter and accumulation of calcium, zinc and phosphorus in the shoot dry matter. The increase provided by the arbuscular mycorrhizal fungi and the use of stimulant reached over 200 % in bean and over 80 % in soybean plants. The fungi Acaulospora scrobiculata, Dentiscutata heterogama, Gigaspora margarita and Rhizophagus clarus, for bean, and Claroideoglomus etunicatum, Dentiscutata heterogama, Rhizophagus clarus and the joint inoculation, for soybean, increased the dry matter and nutrients accumulation.